Hydrostatic pressure induces transformations in the organic matter and microbial community composition of marine snow particles - Peter Stief; Clemens Schauberger; Kevin W. Becker; Marcus Elvert; John Paul Balmonte; Belén Franco-Cisterna; Mathias Middelboe; Ronnie N. Glud (Communications Earth & Environment, 2023)
Abstract In the hadal zone of the ocean (6–11 km), the characteristics of sinking marine snow particles and their attached microbial communities remain elusive, despite their potential importance for benthic life thriving at extreme pressures (60–110 MPa). Here, we used simulation experiments to explore how increasing pressure levels modify the microbial degradation, organic matter composition, and microbiome of sinking diatom aggregates. Individual aggregates were incubated in rotating tanks in which pressure was incrementally increased to simulate a descent from surface to hadal depth within 20 days. Incubations at atmospheric pressure served as controls. With increasing pressure, microbial respiration and diatom degradation decreased gradually and ceased completely at 60 MPa. Dissolved organic carbon leaked substantially from the aggregates at ≥40 MPa, while diatom lipid and pigment contents decreased moderately. Bacterial abundance remained stable at >40 MPa, but bacterial community composition changed significantly at 60–100 MPa. Thus, pressure exposure reduces microbial degradation and transforms both organic matter composition and microbiomes of sinking particles, which may seed hadal sediments with relatively fresh particulate organic matter and putative pressure-tolerant microbes.